Assessment of Health Literacy and Numeracy Among Spanish-speaking Parents of Young Children; Validation of the Spanish Parental Health Literacy Activities Test (PHLAT Spanish) - Yin, H. Shonna (2011)
OBJECTIVE: To assess the health literacy and numeracy skills of Spanish-speaking parents of young children and to validate a new Spanish language health literacy assessment for parents, the Spanish Parental Health Literacy Activities Test (PHLAT-10 Spanish). DESIGN/METHODS: Cross-sectional study of Spanish-speaking caregivers of young children (<30 months) enrolled at primary care clinics in 4 academic medical centers. Caregivers were administered the 10-item PHLAT in addition to validated tests of health literacy (S-TOFHLA) and numeracy (WRAT-3 Arithmetic). Psychometric analysis was used to examine item characteristics of the PHLAT-10 Spanish, to assess its correlation with sociodemographics and performance on literacy/numeracy assessments, and to generate a shorter 8-item scale (PHLAT-8). RESULTS: Of 176 caregivers, 77% had adequate health literacy (S-TOFHLA), while only 0.6% had 9(th) grade or higher numeracy skills. Mean PHLAT-10 score was 41.6% (SD 21.1). Fewer than half (45.5%) were able to read a liquid antibiotic prescription label and demonstrate how much medication to administer within an oral syringe. Less than a third (31.8%) were able to interpret a food label to determine whether it met WIC guidelines. Higher PHLAT-10 score was associated with higher years of education (r=0.49), S-TOFHLA (r=0.53) and WRAT-3 (r=0.55) scores (p<0.001). Internal reliability was good (KR-20=0.61). An 8-item scale was highly correlated with the full 10-item scale (r=0.97, p<0.001), with comparable internal reliability (KR-20= 0.64). CONCLUSIONS: Many Spanish-speaking parents have difficulty carrying out health-related literacy and numeracy tasks. The Spanish PHLAT demonstrates good psychometric characteristics and may be useful for identifying parents who would benefit from receiving low-literacy child health information.